Blockchain and Legal Authority: Decentralization, Regulation, and Legitimacy in the Age of Code - Pusca, Andy (Acta Universitatis Danubius. Juridica, 2025)
The article looks at how blockchain technology is reshaping the foundations of legal authority, focusing on the emergence of post-institutional law and the transformation of sovereignty, legitimacy, and regulatory framework. It is based on the literature on “Lex Cryptographia” (Wright & De Filippi, 2015), decentralized governance models and hybrid regulatory approaches, critically assessing their relevance in the current legal context. Using doctrinal analysis and a comparative review of the literature, the study integrates perspectives from law, technology and governance theory. The results highlight the shift from state-centric legal authority to algorithmically executed norms, the coexistence of pluralistic normative systems, and the emergence of hybrid governance models that combine code-based rules with traditional law safeguards. These transformations challenge the established concepts of jurisdiction, liability and legitimacy, with important implications for legislators, courts and international governance bodies. The article proposes an interpretive framework for understanding the legal implications of blockchain and advocates a balanced integration of technological innovation with fundamental principles of law, in order to preserve fairness and accountability in decentralized environments.